Angiojet™ mechanical thrombectomy‐induced hemolysis triggering blood‐leak alarms. Issue 2 (3rd February 2023) - Selvananthan, Babitha; Aziz, Omar; Lee, Arvind D.; Werner‐Gibbings, Keagan; Bose, Bhadran; Sud, Kamal
Abstract: Blood leak alarms are increasingly rare and may be triggered by rupture of the dialyzer membrane, or intravascular hemolysis. We report two patients who developed hemolysis following Angiojet™ thrombolysis and thrombectomy of thrombosed arteriovenous fistulas, triggering blood leak alarms on hemodialysis, the occurrence of which has not been reported before. AngioJet™‐induced hemolysis should be considered in the differential diagnosis for blood leak alarms occurring soon after an intervention on an arterio‐venous (AV) fistula.